2019
DOI: 10.3390/jcm9010059
|View full text |Cite
|
Sign up to set email alerts
|

Ulmus parvifolia Accelerates Skin Wound Healing by Regulating the Expression of MMPs and TGF-β

Abstract: Ulmus parvifolia is one of the medicinal plants used traditionally for treatment of wounds. We intended to investigate the wound healing effect of the powder of Ulmus parvifolia (UP) root bark in a mouse wound healing model. We also determined the mechanisms of effects of U. parvifolia in skin and skin wound healing effects using a keratinocyte model. Animal experiments showed that the wound lesions in the mice decreased with 200 mesh U. parvifolia root bark powder and were significantly reduced with treatment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The stem or root bark has been traditionally used for inflammation and gastric diseases 13 . Recent studies have shown antioxidant, anti-inflammatory, and skin wound healing effects of Ulmus parvifolia 14 , 15 . Catechin-7- O -α-L-rhamnopyranoside (C7R), a catechin glycoside has been isolated as a major component from the stem bark of Ulmus parvifolia .…”
Section: Introductionmentioning
confidence: 99%
“…The stem or root bark has been traditionally used for inflammation and gastric diseases 13 . Recent studies have shown antioxidant, anti-inflammatory, and skin wound healing effects of Ulmus parvifolia 14 , 15 . Catechin-7- O -α-L-rhamnopyranoside (C7R), a catechin glycoside has been isolated as a major component from the stem bark of Ulmus parvifolia .…”
Section: Introductionmentioning
confidence: 99%
“…The bark has the value of demulcent, diuretic, expectorant and febrifuge. 2–4 Additionally, modern medical studies have proved that bark of U. parvifolia have the functions of antioxidant, anti-inflammatory, 5 anti-obesity, 6 anti-platelet, 7 anti-cancer, 8 skin wound healing, 9 and protection of allergic asthma activities. 10 …”
Section: Introductionmentioning
confidence: 99%
“…5 The skin protects against environmental factors such as harmful UV rays and pathogens and prevents water loss. 6 Wound healing is one of the functions of skin. 7 Wound healing maintains homeostasis.…”
Section: Introductionmentioning
confidence: 99%